California Theatre lobby. - Gordon, John C. (photographer):::Creator::::::::::::
California Theatre lobby, one of 1920's motion picture houses. Photograph shows Native American murals on the walls, patterned carpeting and plaster ornamentation. Two arches leading towards the inner theatre dominate the photograph along with a flower and diamond pattern ornamental ceiling. The California Theatre was designed by architects, William Day and Charles Peter Weeks from the "Weeks and Day Firm."